(untitled) (Eurasian Research Bulletin, 2023)
The education system is a crucial aspect of the socio-economic development of a country. In Uzbekistan, the government places significant emphasis on the advancement of education and strives to enhance its quality. In this context, Uzbekistan’s participation in the Programme for International Student Assessment (PISA) represents a strategically important step towards improving the education system and achieving global standards. This article will examine the impact of the PISA program on the assessment of the quality of education in the Republic of Uzbekistan